Marine, Freshwater, and Wetlands Biodiversity Conservation - Hawksworth, David L.; Bull, Alan T. (Topics in Biodiversity and Conservation, 2006)
Marine, coastal and wetland habitats are threatened, not only through exploitation, but also by the prospect of climate change - as ocean currents change course, sea levels rise, and rainfall patterns change. Even the once-common cod is now under threat from the combined effects of over-fishing and a dramatic change-induced decrease in the plankton that cod larvae feed on. Meanwhile, coral reefs remain especially vulnerable to rapid sea-level changes exacerbated by the effects of tourism and disease. This book gathers together a wide range of papers reporting on key research into the biodiversity conservation of these critical and increasingly threatened habitats. Collectively these papers provide a snap-shot of the types of problems they are experiencing, and offer a wealth of topical examples which render this volume especially valuable to teachers of courses in marine, freshwater and wetlands ecology, biological conservation and ecological restoration. Reprinted from Biodiversity and Conservation 15:11 (2006).